2012
DOI: 10.1016/j.sjbs.2012.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and histological impact of Vernonia amygdalina supplemented diet in obese rats

Abstract: This study was carried out to evaluate the anti-obesity effect of Vernonia amygdalina Del. (VA) supplemented diet. VA leaf powder was fed at 5% and 15% to diet-induced obese rats for 4 weeks and its effect compared with orlistat (5.14 mg/kg p.o.), an anti-obesity drug. Food intake, body and organ weights, total body fat, some lipid components and amino transaminase activities in serum, hepatocytes and brain; as well as serum glucose, were measured during or at end of the study. Result showed respective decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 16 publications
6
11
0
Order By: Relevance
“…Two representative anti-obesity drugs, Orlistat and Sibutramine, have been reported to increase in both AST and ALT levels in high fat diet-induced animal even if they have beneficial effects toward suppressing obesity. 24,25) Our result also showed the upregulation of AST in Orlistat-treated mice in accordance with previous literatures. In comparison, serum AST and ALT levels, the hepatotoxicity markers, were significantly decreased in D. oppositifolia-treated high-fat diet-fed mice at end of the study.…”
Section: Discussionsupporting
confidence: 93%
“…Two representative anti-obesity drugs, Orlistat and Sibutramine, have been reported to increase in both AST and ALT levels in high fat diet-induced animal even if they have beneficial effects toward suppressing obesity. 24,25) Our result also showed the upregulation of AST in Orlistat-treated mice in accordance with previous literatures. In comparison, serum AST and ALT levels, the hepatotoxicity markers, were significantly decreased in D. oppositifolia-treated high-fat diet-fed mice at end of the study.…”
Section: Discussionsupporting
confidence: 93%
“…Vernonia amygdalina is a small shrub typical from tropical Africa. Its leaf powder was added to the diet of dietinduced obese rats for 4 weeks and resulted in a decrease of body weight gain, serum triacylglycerol, serum and brain total cholesterol; effects were stronger than by the antiobesity drug orlistat also tested in this study [201]. Administration of pu-erh tea in rats with high fat dietinduced obesity significantly reduced the total body weight, plasma total cholesterol, triglyceride concentrations and lowdensity lipoprotein-cholesterol, suggesting an attenuating effect on fat levels and accumulation [202].…”
Section: From Leavesmentioning
confidence: 75%
“…At the dose of 500 mg/kg body weight, significant beneficial effects were reported in various physiological/histological parameters altered during diabetic VA supplemented diet was evaluated by Item et al [16] for the anti-obesity, and found that plant diet also exerted hepato-protection via lowering serum alanine amino transaminase (41.35% and 27.13%) and aspartate amino transaminase (17.09% and 43.21%) activities (P < 0.05). Khang et al [17] investigated and confirmed the hypoglycemic properties of Vernonia amygdalina and its possible mechanisms of action in a single-dose streptozotocin induced diabetic rat model that might most probably be through increasing glucose transporter 4 translocation and inhibiting hepatic glucose-6-phosphatase.…”
Section: Introductionmentioning
confidence: 99%